Trans-pars-planar illumination enables a 200° ultra-wide field pediatric fundus camera for easy examination of the retina - Toslak, Devrim (Biomed Opt Express, 2019)
This study is to test the feasibility of using trans-pars-planar illumination for ultra-wide field pediatric fundus photography. Fundus examination of the peripheral retina is essential for clinical management of pediatric eye diseases. However, current pediatric fundus cameras with traditional trans-pupillary illumination provide a limited field of view (FOV), making it difficult to access the peripheral retina adequately for a comprehensive assessment of eye conditions. Here, we report the first demonstration of trans-pars-planar illumination in ultra-wide field pediatric fundus photography. For proof-of-concept validation, all off-the-shelf optical components were selected to construct a lab prototype pediatric camera (PedCam). By freeing the entire pupil for imaging purpose only, the trans-pars-planar illumination enables a 200° FOV PedCam, allowing easy visualization of both the central and peripheral retina up to the ora serrata. A low-cost, easy-to-use ultra-wide field PedCam provides a unique opportunity to foster affordable telemedicine in rural and underserved areas.